4-(1H-Tetrazol-5-yl)-2-(p-tolyl)quinoline - Angelika Lásiková; Daniel Végh (Molbank)
The synthesis of 4-(1H-tetrazol-5-yl)-2-(p-tolyl)quinoline 4 as a possible modification of the biphenyltetrazole substructure of losartan 1 is described. The transformation of 2-(p-tolyl)quinoline-4-carbonitrile 3 to the corresponding tetrazole 4 was carried out by the reaction of trimethysilyl azide and dibutyltin oxide as a catalyst in refluxing toluene. The title compound (4) was characterized by IR, 1H NMR, 13C NMR, and HRMS.